Redefining the N-Terminal Regulatory Region of the Ca2+/H+ Antiporter CAX1 in Tomato - Han, Beibei; Tai, Yuxin; Li, Shuping; Shi, Junmei; Wu, Xueqing; Kakeshpour, Tayebeh; Weng, Jianfeng; Cheng, Xianguo; Park, Sunghun; Wu, Qingyu (Frontiers in Plant Science, 2022)
Calcium (Ca2+) is an essential plant nutrient, and Ca2+/H+ exchangers (CAXs) regulate Ca2+ partitioning between subcellular compartments. AtCAX activity is inhibited by its N-terminal regulatory region (NRR), which was initially defined as the sequence between the first two methionines. However, the accuracy of this NRR definition and the NRR regulatory mechanism remain unclear. Here, using tomato SlCAX1 as a model, we redefined the NRR of CAXs and demonstrated that our new definition is also applicable to Arabidopsis AtCAX1 and AtCAX3. The N-terminal-truncated SlCAX1 (SlCAX139) but not the full-length SlCAX1 was active in yeast, similar to Arabidopsis AtCAX1. Characterization of slcax1 mutants generated by CRISPR-Cas9 confirmed the calcium transport ability of SlCAX1. Sequence alignment between SlCAX1, AtCAX1, AtCAX3, and the Bacillus subtilis Ca2+/H+ antiporter protein YfkE revealed that SlCAX1 does not have the 2nd methionine and YfkE does not have any amino acid residues in front of the first transmembrane domain. Truncating the amino acid residues up to the first transmembrane of SlCAX1 (SlCAX166) further increased its activity. The same truncation had a similar effect on Arabidopsis AtCAX1 and AtCAX3. Expression of full-length SlCAX1 and SlCAX166 in tomato plants confirmed the results. Our results suggest that SlCAX1 is critical for Ca2+ homeostasis and all the amino acid residues in front of the first transmembrane domain inhibit the activity of CAXs. Our redefinition of the NRR will facilitate fine-tuning of Ca2+ partitioning to reduce the incidence of Ca2+-related physiological disorders in crops.